The discovery and optimization of naphthalene-linked P2-P4 Macrocycles as inhibitors of HCV NS3 protease. Issue 1 (1st January 2018) - Bowsher, Michael; Hiebert, Sheldon; Li, Rongti; Wang, Alan X.; Friborg, Jacques; Yu, Fei; Hernandez, Dennis; Wang, Ying-Kai; Klei, Herbert; Rajamani, Ramkumar; Mosure, Kathy; Knipe, Jay O.; et al.
Graphical abstract: Abstract: Naphthalene-linked P2-P4 macrocycles within a tri-peptide-based acyl sulfonamide chemotype have been synthesized and found to inhibit HCV NS3 proteases representing genotypes 1a and 1b with single digit nanomolar potency. The pharmacokinetic profile of compounds in this series was optimized through structural modifications along the macrocycle tether as well as the P1 subsite. Ultimately a compound with oral bioavailability of 100% in rat, and a long half-life in plasma was obtained. However, compounds in this macrocyclic series exhibited cardiac effects in an isolated rabbit heart model and for this reason further optimization efforts were discontinued.